PENGARUH PENGELUARAN PEMERINTAH DAN JUMLAH PENDUDUK TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI MAKASSAR - Ikram, Muhammad; IRMA, IRMA (Perpustakaan dan Penerbitan Unismuh Makassar, 2017)
The purpose of this study is to find out variables that have a significant influence on Local Revenue in the city of Makassar. The type of research used is quantitative research, with data collection methods using documentation taken from the Central Bureau of Statistics of South Sulawesi province and related agencies. Data taken in the form of data from 2011-2015, and data processing techniques using multiple linear regression with the help of software SPSS 16 windows. The results of the analysis in this study can be concluded, together Variable Consumption of the Government and the Number of Population fositif and significant effect on the Original Revenue. Partially, only expenditure variable that has no significant effect on Local Own Revenue (PAD) Makassar City. The number of residents is one of the factors that have the highest influence, therefore there should be a government program that can increase the immigrants from other areas, especially in South Sulawesi Island to Makassar city, so that the city of Makassar is not only a transit city but also the City of choice to do economic activity.